Pro-Health and Functional Properties of Goji Berry (Lycium Spp.) - Szot, Iwona; Zhurba, Mykhailo; Klymenko, Svitlana (Agrobiodiversity for Improving Nutrition, Health and Life Quality, 2020)
Goji fruit has been an important element of traditional Chinese medicine for centuries. In Asian countries, they are used as an essential component of a healthy diet, which is a source of many nutrients. Due to their health-promoting properties and chemical composition (phenolic acids, flavonoids, pro-anthocyanidins, coumarins, tannins, carotenoids, anthocyanins), they deserved the term superfruit. In recent years, goji berries have also become very popular in Europe and America. The fruit is used primarily after drying and is available in the form of various supplements. Two species of L. barbarum and L. chinense are cultivated on a larger scale. Not only fruits contain biologically active substances, but also other parts of plants, especially leaves. This review highlights the healing properties of the fruit and leaves of these species. The diversity of their use as food, medicinal and cosmetic agents was shown.